Evaluation of Enzyme Activity and Nutrient Content of Fermented Coconut Meal as a Feed Using Indigenous Microorganisms - Dwi Triani, Hera; Gusri Yanti; Wulansih Dwi Astuti; Sri Suharti; Yetti Marlida (ANIMAL PRODUCTION, 2025)
Coconut pulp has potential as animal feed but is limited in poultry diets due to its high fiber content and low protein levels. Fermentation using indigenous microorganisms offers a practical approach to improving its nutritional value. This study aimed to evaluate the nutritional quality of coconut meal using indigenous microorganisms (IMOs). The initial phase of the study involved producing IMOs, followed by measuring pH, total colony, and cellulase and mannanase enzyme activities. IMOs were applied to ferment coconut meal using a completely randomized design with four treatments (0, 7, 14, and 21 days) and four replications. Observed parameters included cellulase and mannanase enzyme activities, pH, crude fiber, crude protein, crude fat, and nitrogen-free extract. The characteristics of IMOs were analyzed descriptively, while enzyme activities and the nutritional content of coconut meal were analyzed using ANOVA and Duncan’s Multiple Range Test. The results showed that IMOs had a pH of 3.3, were dominated by lactic acid bacteria with a total colony of 5.4 × 10¹² CFU/mL, had cellulase activity of 2.1 U/mL, and had mannanase activity of 7.73 U/mL. Cellulase activity at 7, 14, and 21 days was significantly higher (P<0.01), while mannanase activity was highest at 21 days (P<0.01), with the lowest pH observed at 14 and 21 days. The lowest crude fiber and crude fat content, as well as the highest crude protein content (P<0.01), were observed at 14 days of fermentation. Fourteen days of fermentation were identified as the optimal duration for enhancing the nutritional quality of coconut pulp.